Consumer values for sustainability: a study with the students from accounting of Universidade Federal de Santa Maria - Motke, Francies Diego; Rosa, Luciana Aparecida Barbieri da; Lengler, Letícia; Mainardi, Jeanne; Trevisan, Marcelo (Revista de Administração da UFSM, 2016)
Lately it is demanded to re-evaluate the consumer behavior and their ways of consumption, since each day it is realized a higher need of awareness about what is being consumed as an attempt to reach and to build a more balanced world – with less waste and environmental impact. In this sense, this study goal is to analyze the sustainable consumption behavior of the students from Accounting of UFSM. Therefore, the survey method was used, with a sample by accessibility characterized as non-probabilistic throughout applying a questionnaire that obtained a return of 442 respondents. The data collect instrument was adapted from the study carried by Biswas and Roy (2015) and it approaches the consumption values theory, composed by functional value, social value, conditional value, environmental value and knowledge value. The results from the UFSM students corroborate with Biswas and Roy (2015) findings: the conditional value followed by the environmental values are the key factors that influence the sustainable consumption behavior, and this indicates that changes in the students economic situation may affect the acquisition for green products and the students are aware of how the environment is affected by their consumption habits.